The Existence of Courts and Parliaments in Regional Organizations: A~Case of Democratic Control? - Anja Jetschke; Sören Münch (Politische Vierteljahresschrift, 2020)
Why do states design regional organizations with courts and parliaments? Is it indeed the case that states establish them because they expect these organs to exert some kind of democratic control over executives? Undoubtedly, this is an important question given that politicians and political scientists alike regularly lament the lack of democratic control of many international organizations. We tackle this question empirically. Based on an original data set of 72~regional organizations and by using simple logistic and ordinal logistic regression analyses, this article tests for the association between domestic regime type and the existence of regional courts and parliaments. These organs were selected because they are associated with dimensions of democracy, namely constitutionality and inclusiveness. The most consistent correlates of the existence of each of these institutional bodies and the aggregate of them are functional ones: policy scope, trade-related variables, and conflict-related variables. There is no significant association between any measure of democracy and the existence of these institutions. These results are discussed the context of debates about the democratic deficit of international and regional organizations and the question of whether democratic standards are applicable to regional organizations.
Keywords: 320; International organizations; Democratic deficit; Institutional design; Democracy; Courts; Internationale Organisationen; Demokratiedefizit; Institutionelles Design; Demokratie; Gerichtshöfe